Conservatively treated, live, 12-week cervical pregnancy - case report - Jakub Mlodawski; Anna Chabik; Maciej Albrzykowski; Marta Mlodawska; Grzegorz Swiercz (Kazimierz Wielki University, 2022)
Cervical pregnancy is one of the rarest forms of ectopic pregnancy. Due to the low prevalence of this pregnancy complications, the management of this complication is not standardized. In this work, we describe conservative management of a 12-week cervical pregnancy. Descriptions of the cases of such a large pregnancy treated conservatively are scarce. In order to protect the fertility of the patient, most of the described conservative procedures available in the literature were applied, such as: the administration of a 15% solution of KCl into the gestational sac, administration of methotrexate into the gestational sac and intramuscularly, as well as embolization of the uterine arteries with cervical canal curettage. After 5 weeks of observation and applied treatment, the patient was discharged home with a preserved uterus.